Uma caracterização de potenciais hiperbolicos para mapas racionais - SOUSA, Marcus Vinícius (2020)
In this work we study properties of hyperbolic potentials.We consider maps f : X → X of degree n ≥ 2 with X being compact metric space.We characterize the continuous H¨older potentials ϕ that have the following property sup ϕ < P(f, ϕ).